2000
DOI: 10.2460/javma.2000.217.509
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory responses and plasma cortisol concentrations in dogs treated with medetomidine before undergoing ovariohysterectomy

Abstract: Administration of medetomidine reduced dose requirements for thiopental and halothane and provided postoperative analgesia up to 90 minutes after extubation. Dogs undergoing ovariohysterectomy by use of thiopental induction and halothane anesthesia benefit from analgesia induced by medetomidine administered prior to anesthesia induction. Additional analgesia is appropriate 60 minutes after extubation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
26
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 12 publications
6
26
0
3
Order By: Relevance
“…The results from this study have demonstrated that the determination of the levels of gylcemia and cortisol is an efficient method to evaluate nociceptive stimulus in dogs; similar results have been previously described (AMBRISKO; HIKASA; SATO, 2005;KO et al, 2000;FANTONI, 2001;VAISANEN et al, 2002). The results of the evaluation of cortisol by Chemiluminescent Enzyme Immunoassay were similar to those obtained by others who utilized the radioimmunoassay (AMBRISKO; HIKASA; SATO, 2005;FOX et al, 1994;SOUZA et al, 2001) and floruoimmunoessay (MASTROCINQUE, 2005) techniques in studies realized to evaluate the efficiency of drugs for nociceptive control (FOX et al, 1994;SOUZA et al, 2001); consequently, this method can be considered as adequate and efficient to evaluate the hormone in question.…”
Section: Discussionsupporting
confidence: 69%
“…The results from this study have demonstrated that the determination of the levels of gylcemia and cortisol is an efficient method to evaluate nociceptive stimulus in dogs; similar results have been previously described (AMBRISKO; HIKASA; SATO, 2005;KO et al, 2000;FANTONI, 2001;VAISANEN et al, 2002). The results of the evaluation of cortisol by Chemiluminescent Enzyme Immunoassay were similar to those obtained by others who utilized the radioimmunoassay (AMBRISKO; HIKASA; SATO, 2005;FOX et al, 1994;SOUZA et al, 2001) and floruoimmunoessay (MASTROCINQUE, 2005) techniques in studies realized to evaluate the efficiency of drugs for nociceptive control (FOX et al, 1994;SOUZA et al, 2001); consequently, this method can be considered as adequate and efficient to evaluate the hormone in question.…”
Section: Discussionsupporting
confidence: 69%
“…Therefore, the effect of medetomidine on glucose concentrations should not be significant and could not influence the definitive pain assessment. The cortisol plasma concentration is not influenced by medetomidine administration (Ko et al 2000). Moreover, a similar dose of medetomidine was administered in all groups.…”
Section: Discussionmentioning
confidence: 93%
“…These can be delivered in combination with analgesics. 111,129,[152][153][154][155] Total IM anesthesia Administering a single injection that includes sedative, analgesic, and anesthetic induction agents may reduce patient pain and stress, compared with administering multiple injections. Combining premedications and anesthetic induction agents in a single injection is a useful technique for some spay-neuter programs.…”
Section: Administration Of Analgesics and Anxiolyticsmentioning
confidence: 99%